Synthesis and crystal structure of layer perovskites Sr3LnBIIISnO8 (BIII — Sc, In) - Titov, Y. A.; Belyavina, N. M.; Markiv, V. Ya.; Slobodyanik, M. S.; Polybinskii, V. V. (Reports of the National Academy of Sciences of Ukraine, 2014)
The boundaries of the morphotropic transition in the Sr3LnBIIISnO8 (BIII — Sc, In) monoslab perovskites with layer perovskite-like structures (LPS) have been defined. The Sr3LnInSnO8 (Ln — La, Pr, Nd) and Sr3LaScSnO8 compounds have been synthesized, and their LPS is determined by X-ray powder diffraction. It is found that the LPS of Sr3LnInSnO8 (Ln — La, Pr, Nd) and Sr3LaScSnO8 belong to the SrLaInO4-type structure (sp. gr. Pbca). The final RB values are equal to 0.055–0.063. The peculiarities of LPS for Sr3LnInSnO8 (Ln — La, Pr, Nd) and Sr3LaScSnO8 have been analyzed, and the correlations between their composition and constitution of LPS are found.